ANALISIS KETERGANTUNGAN DAERAH DALAM MEWUJUDKAN AKUNTABILITAS PENGELOLAAN KEUANGAN DESA SELAT - Ni Putu Melda Utami Melda; Gede Adi Yuniarta (Universitas Pendidikan Ganesha, 2026)
This study aims to analyze the level of financial dependence of Selat Village on transfer funds from the central government and its implications for the accountability of village financial management. This study uses a quantitative descriptive approach with a village financial dependency ratio analysis method and is supported by qualitative analysis through interviews to examine aspects of accountability including transparency, community participation, and accountability. The data used consists of secondary data in the form of the 2021–2025 Selat Village Revenue Budget Detail Report (APBDes) and primary data obtained through interviews with village officials and the community. The results show that the level of financial dependence of Selat Village on transfer funds is classified as high to very high with an average ratio of 48.55%, which is caused by low Village Original Income (PADes) which only comes from Village-Owned Enterprises (BUMDes). In terms of accountability, transparency and accountability aspects have been implemented quite well through village deliberations, publication of the APBDes, and the use of the Village Financial System (SISKEUDES) application. However, community participation in village financial management is still relatively low and indirect. This study concludes that the high dependence on transfer funds has an impact on the accountability practices of village financial management, so that efforts are needed to strengthen village financial independence through optimization and diversification of PADes and increasing active community participation.